TIGIT/CD47 dual high expression predicts prognosis and is associated with immunotherapy response in lung squamous cell carcinoma. Issue 14 (24th May 2022) - Peng, Yue; Qiu, Bin; Tan, Fengwei; Xu, Jiachen; Bie, Fenglong; He, Huayu; Liu, Lei; Tian, He; Bai, Guangyu; Zhou, Bolun; Li, Yuan; Huai, Qilin; et al.
Abstract: Background: Recent studies indicated that T cell immunoreceptor with immunoglobulin and ITIM domains (TIGIT) and cluster of differentiation 47 (CD47) have emerged as new potential immunotherapy targets. However, the roles of TIGIT and CD47 in lung squamous cell carcinoma (LUSC) have not been fully illustrated. Methods: The specimens and clinicopathological information from 190 LUSC patients who underwent surgeries in our center were retrospectively collected. Immunohistochemical staining for TIGIT and CD47 was conducted. Transcriptional and clinical data of 479 LUSC were downloaded from The Cancer Genome Atlas (TCGA). Results: In the TCGA LUSC cohort, 142 (29.6%) cases were TIGIT/CD47 dual high expression at RNA level. The expression levels of TIGIT and CD47 were significantly correlated ( p  < 0.001). The proportions of patients with high TIGIT expression ( p  = 0.001) and high TIGIT/CD47 dual high expression ( p  = 0.049) were both higher in female cases. Advanced TNM stage ( p  = 0.006) and TIGIT/CD47 dual high expression ( p  = 0.047) were independent prognostic factors for LUSC. In the 190 LUSC cohort of our center, 75 (39.5%) cases were TIGIT/CD47 dual high expression at protein level. Cross‐table analysis showed a correlation between TIGIT and CD47 expression. Older age ( p  = 0.001), advanced TNM stage ( p  < 0.001) and TIGIT/CD47 dual high expression ( p  = 0.046) were independent prognostic factors in our cohort. Conclusion: We found that TIGIT and CD47 dual high expression was associated with poor prognosis in LUSC. We speculated that patients with dual high expression of CD47/TIGIT might be suitable for new target immunotherapy in the future. Abstract : T cell immunoreceptor with Ig and ITIM domains (TIGIT) and cluster of differentiation 47 (CD47) have emerged as new potential immunotherapy targets. They might play synergistic roles in the immune escape of tumors. We demonstrated the expression status of TIGIT and CD47 in lung squamous cell carcinoma (LUSC) based on two independent cohorts from TCGA database and our center, and found that the expression level of TIGIT and CD47 were closely related at both RNA and protein level. TIGIT/CD47 dual high expression was an independent prognostic factor for LUSC. We speculated that patients with dual high expression of TIGIT/CD47 might be suitable for new target combined immunotherapy in the future.